Neuroendocrine subtypes of small cell lung cancer differ in terms of immune microenvironment and checkpoint molecule distribution. Issue 9 (18th July 2020) - Dora, David; Rivard, Christopher; Yu, Hui; Bunn, Paul; Suda, Kenichi; Ren, Shengxiang; Lueke Pickard, Shivaun; Laszlo, Viktoria; Harko, Tunde; Megyesfalvi, Zsolt; Moldvay, Judit; Hirsch, Fred R.; et al.
Abstract : Small cell lung cancer (SCLC) has recently been subcategorized into neuroendocrine (NE)‐high and NE‐low subtypes showing 'immune desert' and 'immune oasis' phenotypes, respectively. Here, we aimed to characterize the tumor microenvironment according to immune checkpoints and NE subtypes in human SCLC tissue samples at the protein level. In this cross‐sectional study, we included 32 primary tumors and matched lymph node (LN) metastases of resected early‐stage, histologically confirmed SCLC patients, which were previously clustered into NE subtypes using NE‐associated key RNA genes. Immunohistochemistry (IHC) was performed on formalin‐fixed paraffin‐embedded TMAs with antibodies against CD45, CD3, CD8, MHCII, TIM3, immune checkpoint poliovirus receptor (PVR), and indoleamine 2, 3‐dioxygenase (IDO). The stroma was significantly more infiltrated by immune cells both in primary tumors and in LN metastases compared to tumor nests. Immune cell (CD45 + cell) density was significantly higher in tumor nests ( P  = 0.019), with increased CD8 + effector T‐cell infiltration ( P  = 0.003) in NE‐low vs NE‐high tumors. The expression of IDO was confirmed on stromal and endothelial cells and was positively correlated with higher immune cell density both in primary tumors and in LN metastases, regardless of the NE pattern. Expression of IDO and PVR in tumor nests was significantly higher in NE‐low primary tumors (vs NE‐high, P  < 0.05). We also found significantly higher MHC II expression by malignant cells in NE‐low (vs NE‐high, P  = 0.004) tumors. TIM3 expression was significantly increased in NE‐low (vs NE‐high, P  < 0.05) tumors and in LN metastases (vs primary tumors, P  < 0.05). To our knowledge, this is the first human study that demonstrates in situ that NE‐low SCLCs are associated with increased immune cell infiltration compared to NE‐high tumors. PVR, IDO, MHCII, and TIM3 are emerging checkpoints in SCLC, with increased expression in the NE‐low subtype, providing key insight for further prospective studies on potential biomarkers and targets for SCLC immunotherapies. Abstract : Small cell lung cancer (SCLC) has recently been subcategorized into neuroendocrine (NE)‐high and NE‐low subtypes. This study demonstrates that NE‐low SCLCs are associated with increased immune‐cell infiltration compared to NE‐high tumours. We found expression of PVR, indoleamine 2, 3‐dioxygenase, MHCII, and TIM3 to be increased in the NE‐low subtype, highlighting these molecules as potential biomarkers and targets for SCLC immunotherapies.